Overall Survival With Maintenance Olaparib at a 7-Year Follow-Up in Patients With Newly Diagnosed Advanced Ovarian Cancer and a BRCA Mutation: The SOLO1/GOG 3004 Trial. Issue 3 (9th September 2022) - DiSilvestro, Paul; Banerjee, Susana; Colombo, Nicoletta; Scambia, Giovanni; Kim, Byoung-Gie; Oaknin, Ana; Friedlander, Michael; Lisyanskaya, Alla; Floquet, Anne; Leary, Alexandra; Sonke, Gabe S.; Gourley, Charlie; et al.
Abstract : PURPOSE: In SOLO1/GOG 3004 (ClinicalTrials.gov identifier: NCT01844986 ), maintenance therapy with the poly(ADP-ribose) polymerase inhibitor olaparib provided a sustained progression-free survival benefit in patients with newly diagnosed advanced ovarian cancer and a BRCA1 and/or BRCA2 (BRCA) mutation. We report overall survival (OS) after a 7-year follow-up, a clinically relevant time point and the longest follow-up for any poly(ADP-ribose) polymerase inhibitor in the first-line setting. METHODS: This double-blind phase III trial randomly assigned patients with newly diagnosed advanced ovarian cancer and a BRCA mutation in clinical response to platinum-based chemotherapy to maintenance olaparib (n = 260) or placebo (n = 131) for up to 2 years. A prespecified descriptive analysis of OS, a secondary end point, was conducted after a 7-year follow-up. RESULTS: The median duration of treatment was 24.6 months with olaparib and 13.9 months with placebo, and the median follow-up was 88.9 and 87.4 months, respectively. The hazard ratio for OS was 0.55 (95% CI, 0.40 to 0.76; P = .0004 [ P < .0001 required to declare statistical significance]). At 7 years, 67.0% of olaparib patients versus 46.5% of placebo patients were alive, and 45.3% versus 20.6%, respectively, were alive and had not received a first subsequent treatment (Kaplan-Meier estimates). The incidence of myelodysplastic syndrome and acute myeloid leukemia remained low, and new primary malignancies remained balanced between treatment groups. CONCLUSION: Results indicate a clinically meaningful, albeit not statistically significant according to prespecified criteria, improvement in OS with maintenance olaparib in patients with newly diagnosed advanced ovarian cancer and a BRCA mutation and support the use of maintenance olaparib to achieve long-term remission in this setting; the potential for cure may also be enhanced. No new safety signals were observed during long-term follow-up.